Comparison of Computerised and Pencil-and-Paper Neuropsychological Assessments in Older Culturally and Linguistically Diverse Australians. (10th November 2022) - Page, Zara A.; Croot, Karen; Sachdev, Perminder S.; Crawford, John D.; Lam, Ben C.P.; Brodaty, Henry; Miller Amberber, Amanda; Numbers, Katya; Kochan, Nicole A.
Abstract: Objectives: Computerised neuropsychological assessments (CNAs) are proposed as an alternative method of assessing cognition to traditional pencil-and-paper assessment (PnPA), which are considered the "gold standard" for diagnosing dementia. However, limited research has been conducted with culturally and linguistically diverse (CALD) individuals. This study investigated the suitability of PnPAs and CNAs for measuring cognitive performance in a heterogenous sample of older, Australian CALD English-speakers compared to a native English-speaking background (ESB) sample. Methods: Participants were 1037 community-dwelling individuals aged 70–90 years without a dementia diagnosis from the Sydney Memory and Ageing Study (873 ESB, 164 CALD). Differences in the level and pattern of cognitive performance in the CALD group were compared to the ESB group on a newly developed CNA and a comprehensive PnPA in English, controlling for covariates. Multiple hierarchical regression was used to identify the extent to which linguistic and acculturation variables explained performance variance. Results: CALD participants' performance was consistently poorer than ESB participants on both PnPA and CNA, and more so on PnPA than CNA, controlling for socio-demographic and health factors. Linguistic and acculturation variables together explained approximately 20% and 25% of CALD performance on PnPA and CNA respectively, above demographics and self-reported computer use. Conclusions: Performances of CALD and ESB groups differed more on PnPAs than CNAs, but caution is needed in concluding that CNAs are more culturally-appropriate for assessing cognitive decline in older CALD individuals. Our findings extend current literature by confirming the influence of linguistic and acculturation variables on cognitive assessment outcomes for older CALD Australians.